Efektifitas Kantor Camat Banuhampu sebagai Instansi Pelayanan Publik dalam Meningkatkan Progres Masyarakat - Maulana Fajri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study is motivated by the important role of sub-district offices as public service institutions in supporting community progress through student internship programs. The objective of this research is to analyze the effectiveness of the Banuhampu Sub-District Office in improving public service quality and community development. This study employed a qualitative descriptive approach using observation, discussions, and direct involvement in public services during the internship period. The results indicate that the Banuhampu Sub-District Office has made efforts to enhance public services through human resource development, increased community participation, and the use of information technology. However, challenges remain in terms of infrastructure limitations and inter-agency coordination. In conclusion, improving public service effectiveness requires strengthening human resources and optimizing coordination mechanisms to better support community progress.